2022 IEEE 18th International Conference on Automation Science and Engineering (CASE) 2022
DOI: 10.1109/case49997.2022.9926499
|View full text |Cite
|
Sign up to set email alerts
|

A reinforcement learning path planning approach for range-only underwater target localization with autonomous vehicles

Abstract: Underwater target localization using range-only and single-beacon (ROSB) techniques with autonomous vehicles has been used recently to improve the limitations of more complex methods, such as long baseline and ultra-short baseline systems. Nonetheless, in ROSB target localization methods, the trajectory of the tracking vehicle near the localized target plays an important role in obtaining the best accuracy of the predicted target position. Here, we investigate a Reinforcement Learning (RL) approach to find the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Whereas most of the attention in deep RL has focused on game theory (e.g., to solve Atari games [14]), the same principles can be used to solve path planning and trajectory optimization. In our previous study [15], we showed that the RL agent 1 can learn a policy with a performance comparable to the analytically derived optimal trajectory. This approach highlighted the potential for tracking marine animals by autonomous underwater vehicles and could enable coordinated fleets of vehicles to localize 1 Data and materials availability: The range-only target localization algorithms with deep RL are available on GitHub: github.com/imasmitja/RLforUTracking and track a set of underwater assets via multi-agent, multitarget approaches that are currently intractable with existing methodologies.…”
Section: A Range-only Target Localizationmentioning
confidence: 84%
“…Whereas most of the attention in deep RL has focused on game theory (e.g., to solve Atari games [14]), the same principles can be used to solve path planning and trajectory optimization. In our previous study [15], we showed that the RL agent 1 can learn a policy with a performance comparable to the analytically derived optimal trajectory. This approach highlighted the potential for tracking marine animals by autonomous underwater vehicles and could enable coordinated fleets of vehicles to localize 1 Data and materials availability: The range-only target localization algorithms with deep RL are available on GitHub: github.com/imasmitja/RLforUTracking and track a set of underwater assets via multi-agent, multitarget approaches that are currently intractable with existing methodologies.…”
Section: A Range-only Target Localizationmentioning
confidence: 84%